The keepers of the 5 kingdoms [videorecording (DVD)] - Hong, James; Underhill, Ace; Ward, Zack, 1970-; Hong, James; Mao, Michelle; Harr, Anna, 2000-; Sato, Matthew, 2001- (Vision Films, 2024)
When Patsy Lee discovers an ancient relic box, she has no idea that it will transport her, her grandfather, and her friends to a mystical world of vampires, goblin witches, talking turtles, and an evil sorceress who will stop at nothing to get the box. Their only chance of returning home is to stop her before she finds the key to the 5 Kingdoms and destroys the entire world.